2016
DOI: 10.1097/nmc.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Visits

Abstract: The Virtual Visit program provides low-risk pregnant women with a new model of prenatal care that does not appear to demonstrate increased risk for mother or baby compared to a traditional model. This program may be especially appealing to middle-/high-income mothers who are partnered and already have children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 18 publications
2
79
0
2
Order By: Relevance
“…Three women were recalled to the hospital due to suspicious f-ECG, of which in 2 cases caesarean section was indicated. A Virtual Obstetric Care program with normal visits combined with teleconferencing visits for low-risk pregnancy showed no increased risks in health outcomes besides an increase in preeclampsia diagnosis [ 74 ]. Another demonstration project describes a promising system of a wirelessly enabled maternal-fetal monitoring system MiBebe , used for the improvement of perinatal care in rural regions in Mexico.…”
Section: Resultsmentioning
confidence: 99%
“…Three women were recalled to the hospital due to suspicious f-ECG, of which in 2 cases caesarean section was indicated. A Virtual Obstetric Care program with normal visits combined with teleconferencing visits for low-risk pregnancy showed no increased risks in health outcomes besides an increase in preeclampsia diagnosis [ 74 ]. Another demonstration project describes a promising system of a wirelessly enabled maternal-fetal monitoring system MiBebe , used for the improvement of perinatal care in rural regions in Mexico.…”
Section: Resultsmentioning
confidence: 99%
“…13 The potential benefits of virtual visits in the setting of the COVID-19 pandemic may further support provision of telehealth services despite well characterized legal, regulatory, liability, and reimbursement hurdles. 13 Prior research has demonstrated comparable outcomes with prenatal telehealth visits, 14 with patients demonstrating satisfaction with virtual visits. 15 A recent systematic review of telehealth interventions in obstetrics and gynecology evaluated 47 studies of which 19 pertained to low-risk obstetrics and 13 pertained to high-risk obstetrics.…”
Section: Discussionmentioning
confidence: 97%
“…Antenatal care is important to monitor mother and baby by doing regular check monthly (Widiasih, Ermi, & Setyawati, 2018). Furthermore, to improve antenatal care, Pflugeisen et al, (2016) developed a new model or program of antenatal care, namely a virtual visit for low-risk pregnant women who interspersed doctor visits directly with nurse practitioner visits through video conferencing. This program may be very relevant to the practice of serving pregnant women in the countryside or pregnant women who live far from their providers.…”
Section: Technology In the Form Of Tools Or Devicesmentioning
confidence: 99%